Perovskite solar cell

By introducing a 2D perovskite seed layer into perovskite solar cells, providing nucleation sites and inducing the high crystallization orientation of FAPbI3, the problems of low crystallinity and poor interface stability of perovskite films are solved, and the photoelectric conversion efficiency and stability of solar cells are significantly improved.

CN119604118APending Publication Date: 2025-03-11SOUTH CHINA NORMAL UNIV

Patent Information

Application Number
CN202411530331.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing perovskite solar cells are difficult to stably form photoactive α-phase FAPbI3 at room temperature, and the perovskite film has low crystallinity, severe ion migration, and harmful voids in the buried interface, which affects its performance.

Method used

A 2D perovskite seed layer is arranged between the electron transport layer and the perovskite layer, and a 2D perovskite seed single crystal is prepared by a specific process and used as a seed layer to provide nucleation sites during the formation of the perovskite layer, inducing the high crystallization orientation of FAPbI3.

Benefits of technology

Through the introduction of 2D perovskite seed layer, the crystallinity and film quality of the perovskite layer are significantly improved, the interface stability is enhanced, and the photoelectric power conversion efficiency (PCE) and long-term stability of solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604118A_ABST
    Figure CN119604118A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell which comprises a conductive glass layer, an electron transport layer, a perovskite layer, a hole transport layer and a metal electrode layer which are stacked, and the perovskite layer is made of FAPbI3; the perovskite solar cell is characterized by further comprising a 2D perovskite seed layer arranged between the electron transport layer and the perovskite layer, and the 2D perovskite seed layer provides a nucleation site for formation of an alpha-FAPbI3 phase of the perovskite layer; the 2D perovskite seed layer is prepared by the following steps: 1) dissolving organic amine, PbO and MACl in a mixed aqueous solution of HI and H3PO2, heating while stirring to react, and then cooling and separating out to obtain a 2D perovskite seed single crystal; and 2) preparing the 2D perovskite seed single crystal into a seed precursor solution, coating the surface of the electron transport layer with the seed precursor solution, and annealing to obtain the 2D perovskite seed layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite photovoltaics, and in particular relates to a perovskite solar cell. Background Art

[0002] Perovskite solar cells (PSCs) have attracted extensive attention in the photovoltaic community due to their excellent semiconductor properties, such as high light absorption coefficient, tunable band gap, and long carrier diffusion length. After years of rapid development, the photoelectric power conversion efficiency (PCE) of PSCs has exceeded 26%, showing great application potential in the photovoltaic field.

[0003] FAPbI3 is often used in high-efficiency PSCs due to its narrower optical band gap. However, FAPbI3 usually exhibits a photoinactive δ phase at room temperature, which requires overcoming a huge energy barrier to transform into the desired photoactive α phase. Therefore, phase transition and crystallization are crucial for the preparation of α-phase FAPbI3 perovskite solar cells.

[0004] However, defect sites and grain boundaries (GBs) in FAPbI3 perovskite bulk are located at buried interfaces, which often become degradation centers and degrade when exposed to moisture, oxygen or other stress sources such as high temperature, light and bias. Moreover, the low crystallinity, severe ion migration and harmful voids at buried interfaces of FAPbI3 perovskite still need urgent attention.

[0005] Therefore, there are reports on highly crystalline modified perovskites in the prior art.

[0006] For example, Chinese patent CN220476238U discloses a surface passivated perovskite solar cell, which sets a passivation layer containing cyclodextrin material on the perovskite layer to enhance the connection between the perovskite layer and the hole transport layer. However, this technology can only perform post-processing on the perovskite layer to passivate the surface defects of the perovskite layer, but does not fully modify the internal defects of the perovskite crystal.

[0007] For example, Chinese patent CN116322093A discloses the introduction of a non-fullerene acceptor material BDT-IC as an interface modification layer between an electron transport layer and a perovskite light absorbing layer, with the purpose of passivating defects at the interface between the electron transport layer and the perovskite. However, the crystallinity of the perovskite film is still low, and a high-quality film cannot be obtained.

[0008] For another example, Chinese patent CN117560979A discloses a method for preparing a perovskite film, in which a two-dimensional perovskite single crystal is doped into a perovskite precursor solution to prepare a three-dimensional perovskite film, and the two-dimensional perovskite single crystal is spin-coated on the surface of the 3D perovskite film. However, the two-dimensional perovskite single crystal material contains fluorine, that is, new impurities are doped into the perovskite film, resulting in a low chemical purity of the perovskite seed, which cannot effectively play a role in inducing crystal seeds, thereby failing to effectively improve the internal defects of the perovskite crystal; in addition, the perovskite film is passivated with a single crystal, and the crystal quality inside it has not been substantially improved, and the crystallinity may still be low.

[0009] In summary, if we can obtain highly oriented and low-defect perovskite films by regulating the crystallization process of FAPbI3-type perovskite materials, it is critical to realize efficient and stable FAPbI3-type perovskite photovoltaic devices. Summary of the invention

[0010] The purpose of the present invention is to provide a perovskite solar cell, which can improve the performance of the solar cell by obtaining a high-quality perovskite layer.

[0011] To achieve the above object, the present invention adopts the following technical solutions.

[0012] A perovskite solar cell comprises a stacked conductive glass layer, an electron transport layer, a perovskite layer, a hole transport layer, and a metal electrode layer, wherein the material of the perovskite layer is FAPbI3; wherein the perovskite solar cell further comprises a 2D perovskite seed layer disposed between the electron transport layer and the perovskite layer, which provides a nucleation site for the formation of an α-FAPbI3 phase of the perovskite layer;

[0013] The 2D perovskite seed layer is prepared by the following steps: 1) dissolving organic amine, PbO and MACl in a mixed aqueous solution of HI and H3PO2, heating under stirring for reaction, and then cooling and precipitating to obtain a 2D perovskite seed single crystal; 2) making the 2D perovskite seed single crystal into a seed precursor solution, coating it on the surface of the electron transport layer, and annealing to obtain a 2D perovskite seed layer.

[0014] The present invention sets a 2D perovskite seed layer on the surface of the electron transport layer in the nip perovskite solar cell structure to provide a nucleation site for the formation of the α-FAPbI3 phase in the perovskite layer; and the 2D perovskite crystal induces [PbI6] 4-The growth of the octahedron on the seed layer realizes the high crystallization orientation of the FAPbI3 perovskite from the bottom to the top. At the same time, the present invention forms a 2D perovskite layer with a single quantum well at the buried interface of the 3D perovskite layer by setting a 2D perovskite seed layer, and the 2D / 3D perovskite constructed thereby can alleviate the interface energy disorder caused by the multiphase structure, which is beneficial to the charge transfer between the electron transport layer and the perovskite active layer. The present invention can also adjust the crystallization process of the perovskite layer through the 2D perovskite seed layer, so that the FAPbI3 film is preferentially oriented and crystallized to optimize the crystal quality. In addition, the 2D perovskite seed single crystal of the present invention has a unique quantum well, high phase purity, and the effect of accurately controlling the concentration, and a FAPbI3 perovskite film with significantly improved film quality and significantly suppressed non-radiative recombination can be obtained.

[0015] As a preferred embodiment of the present invention, the organic amine is cyclopropylcarboxamidine hydrochloride (CPAH, CAS No.: 57297-29-7) or cyclobutanecarbonylamidine hydrochloride (CBAH, CAS No.: 71690-89-6); the organic amine is more preferably CBAH.

[0016] As a preferred embodiment of the present invention, the mixed aqueous solution of HI and H3PO2 is obtained by mixing a HI aqueous solution with a concentration of 57 wt% and a H3PO2 aqueous solution with a concentration of 50 wt% in a volume ratio of 6:1.

[0017] As a preferred embodiment of the present invention, organic amine, PbO and MACl are dissolved in a mixed aqueous solution of HI and H3PO2, so that the concentrations of organic amine, PbO and MACl in the solution are 0.1 mmol / mL, 3 mmol / mL and 0.02 mmol / mL, respectively.

[0018] As a preferred embodiment of the present invention, the heating is gradually heated from room temperature to 240°C at a heating rate of 180 rpm / s; when the temperature reaches 240°C, the reaction is completed, and then cooling is performed for precipitation.

[0019] As a preferred embodiment of the present invention, the thickness of the 2D perovskite seed layer is 200 nm to obtain the optimal photoelectric conversion efficiency.

[0020] As a preferred embodiment of the present invention, the 2D perovskite seed single crystal is added to a DMF solvent at a concentration of 0.08-0.10 mmol / mL and shaken and dissolved on a shaker at room temperature for 7-8 hours to prepare a seed precursor solution. More preferably, the 2D perovskite seed single crystal is added to a DMF solvent at a concentration of 0.10 mmol / mL to prepare a seed precursor solution.

[0021] As a preferred embodiment of the present invention, the coating method of the seed precursor liquid is spin coating, specifically, the seed precursor liquid is pre-spun at 1000 rpm for 5 seconds, and then the liquid film is spun at 5000 rpm for 30 seconds to the electron transport layer, and then transferred to a heating table at 120°C in a nitrogen atmosphere of a glove box, annealed for 30 minutes, to obtain a 2D perovskite seed layer.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] A 2D perovskite seed layer was prepared by using a specific 2D perovskite single crystal. The 2D perovskite seed layer showed a unique template effect, triggering the formation of α-FAPbI3, inducing the growth of the upper perovskite, enhancing the crystal surface contact and improving the interface stability, and promoting the crystallization of the perovskite layer. At the same time, the 2D perovskite seed layer plays a role in connecting the electron transport layer and the perovskite layer, thereby ensuring the transport of the bottom charge. In summary, the purpose of improving the performance of solar cells is ultimately achieved; compared with solar cells without a seed layer, the photovoltaic power conversion efficiency (PCE) of the solar cell of the present invention is increased from 19.95% to 21.98%, and it can still maintain 80% of the initial PCE after being stored for 1992 hours under the conditions of 25% RH and room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are the FTIR spectra of CBAH, (CBA)2PbI4, CPAH, and (CBA)2PbI4.

[0025] Figure 2 XPS spectra of Pb4f, I 3d, and N 1s of FAPbI3 films prepared on no seed layer, (CBA)2PbI4 seed layer, and (CPA)2PbI4 seed layer.

[0026] Figure 3 XRD patterns of (CBA)2PbI4 seed layer and (CBA)2PbI4 seed layer film; XRD patterns of FAPbI3 perovskite layer prepared on no seed layer, (CBA)2PbI4 seed layer and (CPA)2PbI4 seed layer.

[0027] Figure 4 SEM surface and cross-sectional images of FAPbI3 perovskite layers prepared on no seed layer, (CBA)2PbI4 seed layer, and (CPA)2PbI4 seed layer.

[0028] Figure 5 PL spectra of the surface of FAPbI3 perovskite layer prepared on no seed layer, (CBA)2PbI4 seed layer, and (CPA)2PbI4 seed layer.

[0029] Figure 6 JV curves of solar cells prepared based on no seed layer, (CBA)2PbI4 seed layer, and (CPA)2PbI4 seed layer under reverse scanning in Comparative Example 1, Example 3, and Example 4.

[0030] Figure 7 Graph showing the normalized PCE variation over time of the solar cells prepared based on no seed layer, (CBA)2PbI4 seed layer, and (CPA)2PbI4 seed layer in Comparative Example 1, Example 3, and Example 4.

[0031] Figure 8 The random efficiency box plot and the JV curve under reverse scanning of the solar cell prepared based on the (CBA)2PbI4 seed layer and the CBAH seed layer in Comparative Example 2.

[0032] Fig. 9 The random efficiency box plot and JV curve under reverse scanning of the solar cell prepared based on (CBA)2PbI4 seed layer and Mix seed layer in Comparative Example 3.

[0033] Fig.10 The random efficiency box plot and the JV curve under reverse scanning of the solar cell prepared based on the (CBA)2PbI4 seed layer and the CBAH-Add seed layer in Comparative Example 4.

[0034] Fig.11 Optical photographs of perovskite solar cells prepared based on seed precursor solutions with different concentrations after being placed in the N2 atmosphere of a glove box for 3 hours.

[0035] Fig.12 This is a box plot of the photoelectric conversion efficiency of perovskite solar cells prepared based on different amounts of seed precursor solution.

[0036] Fig.13 SEM images of the seed layer and perovskite layer prepared at different annealing temperatures. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1: Confirming the influence of 2D perovskite seed layer on perovskite layer

[0039] Experimental group 1: 2D perovskite seed layer and perovskite layer were prepared according to the following steps:

[0040] (1) Conductive glass layer pretreatment:

[0041] a. After gently rubbing the ITO conductive glass with detergent, ultrasonic cleaning was performed with detergent dilution, deionized water, and isopropanol in sequence, each for 15 minutes, and then blown dry with nitrogen and placed in a UV-ozone cleaner for 15 minutes to remove surface organic solvents.

[0042] (2) Deposition of SnO2 electron transport layer:

[0043] a. Preparation of SnO2 precursor solution: Dissolve 0.4512g SnCl2·H2O crystalline powder in 20mL of n-butanol, sonicate for 1 to 2min to fully dissolve the solid powder, add 2mL of deionized water, heat to 110°C in an oil bath, condense and reflux for 4h, cool to room temperature, and absorb the supernatant to obtain SnO2 precursor solution.

[0044] b. Deposition of SnO2 electron transport layer: Draw the required amount of SnO2 precursor with a syringe, install a filter with a pore size of 0.22μm to filter the precipitate in the precursor, pre-spin the filtered precursor at 500rpm for 3s, then spin coat it on the ITO conductive glass at 3000rpm for 30s, transfer it to a heating table at 150℃ in air, anneal for 45min, and cool to room temperature.

[0045] (3) Preparation of 2D perovskite seed layer:

[0046] a. Preparation of 2D perovskite seed single crystals: 6 mL of 57 wt% HI aqueous solution and 1 mL of 50 wt% H3PO2 aqueous solution were mixed to obtain a mixed aqueous solution of HI and H3PO2, and then the concentrations of 0.1 mmol / mL, 3 mmol / mL, and 0.02 mmol / mL were respectively

[0047] CBAH, PbO and MACl were dissolved in a mixed aqueous solution of HI and H3PO2; in a constant temperature heated magnetic stirrer, the above solution was stirred and heated from room temperature to 240°C, and then cooled and precipitated at room temperature to obtain a 2D perovskite seed single crystal (CBA) 2PbI4 (hereinafter also referred to as 4-SD).

[0048] b. Preparation of seed precursor solution: Dissolve the seed single crystal in DMF solvent at an optimal concentration of 0.1 mmol / mL, shake and mix on a shaker at room temperature for 7 to 8 hours to obtain a seed precursor solution.

[0049] c. Preparation of 2D perovskite seed layer: The ITO / SnO2 substrate prepared in steps (1) and (2) was placed in a UV-ozone cleaner for 20 min, and then the seed precursor solution was heated to 1000 °C.

[0050] The film was pre-spun at rpm for 5 s, and the liquid film was spun onto the SnO2 electron transport layer of the substrate at 5000 rpm for 30 s. The film was transferred to a heating stage at 120 °C in a nitrogen atmosphere of a glove box and annealed for 30 min to obtain a 2D perovskite seed layer with a thickness of 200 nm.

[0051] (4) Preparation of 3D FAPbI3 perovskite layer:

[0052] a. Preparation of FAPbI3 perovskite precursor solution: 5.2 mg MACl, 103.2 mg formamidine hydroiodide (FAI) and 280 mg PbI2 were mixed in a mixed solvent of ethylene glycol methyl ether (2-Me) and N-methylpyrrolidone (NMP) with a total volume of 500 μL. After shaking on a shaker at room temperature for 7 to 8 hours, the mixture was filtered through a filter with a pore size of 0.22 μm and set aside.

[0053] b. Preparation of FAPbI3 perovskite layer: Scrape the precursor solution on the surface of the ITO / SnO2 / 4-SD seed layer substrate and transfer it to the scraper glove box; adjust the scraper height to 1250μm and keep the slit width with the substrate at 150μm; adjust the scraper and substrate edges so that they are three-seamed with the reference edge, and use a pipette to inject 14μL of precursor solution into the slit; set the parameters of the scraper: step length is 45000, step speed is 2800. Turn on the nitrogen air knife switch, control the flow rate at 30L / min, and then start scraping; after scraping, quickly transfer the substrate covered with the perovskite precursor liquid film to a hot stage at 120°C and anneal for 45 minutes to obtain a 3D FAPbI3 perovskite film, that is, a 3D FAPbI3 perovskite layer; obtain the conductive glass layer, electron transport layer, 2D perovskite seed layer and perovskite layer in the solar cell, with a structure of ITO / SnO2 / 4-SD / FAPbI3.

[0054] Experimental Group 2: The steps of Experimental Group 1 were repeated, except that CPAH was used instead of CBAH to prepare 2D perovskite seed single crystal (CPA) 2PbI4 (hereinafter also referred to as 3-SD) to obtain a conductive glass layer, an electron transport layer, a 2D perovskite seed layer and a perovskite layer in a solar cell, and the structure was ITO / SnO2 / 3-SD / FAPbI3.

[0055] Control group: Repeat steps (1) to (2) and (4) of the above experimental group 1 to prepare a conductive glass layer, an electron transport layer and a perovskite layer in a solar cell with a structure of ITO / SnO2 / FAPbI3.

[0056] The products prepared by the above groups were subjected to the following tests:

[0057] ① Test the Fourier transform infrared spectra (FTIR) of the seed layer of (CBA)2PbI4, the seed layer of (CPA)2PbI4, CBAH, and CPAH respectively. The results are as follows Figure 1 shown.

[0058] Depend on Figure 1 (a) It can be seen that CBAH at wave number 3270cm -1 The peak of the NH bond in the synthesized seed single crystal (CBA)2PbI4 moves to a higher wave number of 3354cm -1 , indicating that CBAH and PbI2 have a strong interaction. Figure 1 (b) It can be seen that after CPAH is mixed with PbI2, the peak of the NH bond in CPAH changes from 3311 cm -1 Move to 3357cm -1 , there are also small changes, indicating that CPAH also interacts strongly with PbI2. Since PbI2 comes from the perovskite layer, the above results confirm the interaction between the two 2D perovskite seed single crystals and the perovskite layer.

[0059] ② Use X-ray electron spectroscopy to analyze the perovskite layers prepared by each group. Figure 2 Shown are the XPS graphs of Pb 4f, I 3d, and N 1s corresponding to the FAPbI3 perovskite films prepared on different seed layers (or no seed layer).

[0060] Depend on Figure 2 (a) It can be seen that compared with the control group, the Pb content of the FAPbI3 perovskite film prepared on 4-SD in the experimental group 1 is 2+ The two peaks at 139.8eV and 134.95eV corresponding to 4f 5 / 2 and 4f 7 / 2 shifted to 139.65eV and 134.84eV with lower binding energy, respectively, while the two small peaks at 138.43 and 133.52eV (belonging to Pb 0 4f 5 / 2 and 4f 7 / 2) disappear, which confirms the strong interaction between 4-SD and FAPbI3 perovskite film suppressing the Pb 0 The generation of deep level defects. Figure 2As shown in (b) and (c), the N 1s of the FAPbI3 perovskite film prepared on 4-SD changes from 397.11eV to 396.95eV, I 3d 3 / 2 changes from 627.18eV to 626.95eV, and I 3d5 / 2 changes from 615.73eV to 615.40eV, which further proves the interaction between 4-SD and FAPbI3 perovskite film. This interaction originates from the bonding between the electronegative N in CBAH and the Pb and I in the perovskite, indicating that the reaction between the 4-SD seed layer and the PbI2 in the perovskite layer is more thorough, fully reflecting the inductive effect of the seed layer. For the FAPbI3 perovskite film prepared on 3-SD in experimental group 2, there are the same changes as the control group, but the changes are smaller than those in experimental group 1, that is, 3-SD also interacts with the FAPbI3 perovskite film.

[0061] ③ X-ray diffraction (XRD) was used to characterize the seed layers of experimental groups 1 and 2 and the perovskite layers prepared in each group.

[0062] like Figure 3 As shown in (a), the characteristic diffraction peak of 2D perovskite can be seen at ~7.6°, indicating that 2D perovskite has formed in the seed layer of test groups 1 and 2; the intensity of the 4-SD diffraction peak is significantly greater than that of the 3-SD, indicating that the 4-SD seed single crystal has better crystallization and better performance. Figure 3 (b), by comparing the spectra, it can be found that the intensity of the (110) crystal plane characteristic diffraction peak corresponding to ~14.1° of the 4-SD / FAPbI3 perovskite film prepared in experimental group 1 and the 3-SD / FAPbI3 perovskite film prepared in experimental group 2 is greater than that of the seedless FAPbI3 perovskite film in the control group; that is, compared with the seedless FAPbI3 perovskite film, the FAPbI3 perovskite film deposited on the seed layer has higher crystallinity and higher quality, especially the FAPbI3 perovskite film deposited on the 4-SD seed layer has higher quality.

[0063] ④ The perovskite layers prepared by each group were tested by scanning electron microscope (SEM). The results are as follows: Figure 4 shown.

[0064] Figure 4 (a) shows that although the perovskite layer of the control group is completely covered as a whole, there are some large pinhole defects, and the grain size is generally small. At the same proportional size, there are more grain boundaries, and the size of most grains is about 290nm. Figure 4 (b) shows that after the 3-SD seed layer was introduced into the experimental group 2, the size of the perovskite layer grains was significantly improved, and the pinhole defect problem was also improved. Specifically, the pinhole defects became significantly smaller and the number was reduced. Figure 4(c) shows that when the seed layer 4-SD seed layer is introduced into the experimental group 1, the grain size of the perovskite layer becomes larger and there is no pinhole defect at all. Figure 4 The cross-sectional SEM images of the perovskite layer shown in (g), (h) and (i) also illustrate the above problems, and it can be seen that the introduction of the seed layer improves the quality of the perovskite layer. The significant increase in the grain size of the perovskite layer and the reduction of grain boundaries mean a reduction in defects, an improvement in film quality, and a better improvement in charge transport.

[0065] Figure 5 The introduction of the seed layer leads to a blue shift in the photoluminescence emission peak of the perovskite layer (from 803nm to 795nm and 798nm). These results further illustrate that the non-radiative recombination in the perovskite layer prepared based on the seed layer is reduced, which will facilitate the transport of carriers. Secondly, the luminescence intensity of the perovskite layer modified by the seed layer is significantly enhanced, which also indicates that the radiative recombination is increased, the non-radiative recombination is reduced, the carriers are less captured by defects, and the quality of the perovskite layer is improved.

[0066] Example 2

[0067] The solar cell is prepared according to the following steps, and the structure is: conductive glass layer, SnO2 electron transport layer, 2D perovskite seed layer, perovskite layer, hole transport layer and metal electrode layer.

[0068] (1) Conductive glass layer pretreatment:

[0069] a. After gently rubbing the ITO conductive glass with detergent, ultrasonic cleaning was performed with detergent dilution, deionized water, and isopropanol in sequence, each for 15 minutes, and then blown dry with nitrogen and placed in a UV-ozone cleaner for 15 minutes to remove surface organic solvents.

[0070] (2) Deposition of SnO2 electron transport layer:

[0071] a. Preparation of SnO2 precursor solution: Dissolve 0.4512g SnCl2·H2O crystalline powder in 20mL of n-butanol, sonicate for 1 to 2min to fully dissolve the solid powder, add 2mL of deionized water, heat to 110°C in an oil bath, condense and reflux for 4h, cool to room temperature, and absorb the supernatant to obtain SnO2 precursor solution.

[0072] b. Deposition of SnO2 electron transport layer: Draw the required amount of SnO2 precursor with a syringe, install a filter with a pore size of 0.22μm to filter the precipitate in the precursor, pre-spin the filtered precursor at 500rpm for 3s, and then spin coat it on the ITO conductive glass at 3000rpm for 30s, transfer the substrate to a heating table at 150℃ in air, anneal for 45min, and cool to room temperature.

[0073] (3) Preparation of 2D perovskite seed layer:

[0074] a. Preparation of perovskite seed single crystals: 6 mL of 57 wt% HI aqueous solution and 1 mL of 50 wt% H3PO2 aqueous solution were mixed to obtain a mixed aqueous solution of HI and H3PO2, and then the concentrations of 0.1 mmol / mL, 3 mmol / mL, and 0.02 mmol / mL were respectively

[0075] CBAH, PbO and MACl are dissolved in a mixed aqueous solution of HI and H3PO2; in a constant temperature heating magnetic stirrer, the above solution is stirred and heated from room temperature to 240°C, and then cooled and precipitated at room temperature to obtain a seed single crystal (CBA)2PbI4.

[0076] b. Preparation of 2D perovskite seed precursor solution: 2D perovskite seed single crystals were prepared at an optimal concentration of 0.1

[0077] Mm / mL was dissolved in DMF solvent and mixed for 7 to 8 hours to obtain a perovskite seed precursor solution.

[0078] c. Preparation of 2D perovskite seed layer: spin-coat the precursor liquid on the ITO / SnO2 surface, place the ITO / SnO2 substrate in a UV-ozone cleaner for 20 minutes, then pre-spin the precursor liquid at 1000 rpm for 5 seconds, and then spin-coat the liquid film on the substrate at 5000 rpm for 30 seconds. Transfer the substrate to a heating table at 120°C in the N2 atmosphere of the glove box and anneal for 30 minutes to obtain a 2D perovskite seed layer with a thickness of 200 nm.

[0079] (4) Preparation of 3D FAPbI3 perovskite layer:

[0080] a. Preparation of FAPbI3 perovskite precursor solution: 5.2 mg MACl, 103.2 mg formamidine hydroiodide (FAI) and 280 mg PbI2 were mixed in a mixed solvent of ethylene glycol methyl ether (2-Me) and N-methylpyrrolidone (NMP) with a total volume of 500 μL. After shaking on a shaker at room temperature for 7 to 8 hours, the mixture was filtered through a filter with a pore size of 0.22 μm and set aside.

[0081] b. Preparation of FAPbI3 perovskite layer: Scrape the precursor on the surface of ITO / SnO2 / 4-SD seed layer. The ITO / SnO2 / 4-SD seed layer substrate does not need to be cleaned by UV-ozone. Transfer the substrate to the scraper glove box. Adjust the scraper height to 1250μm and keep the slit width between the scraper and the substrate at 150

[0082] μm. Adjust the scraper and the edge of the substrate to align with the reference edge, and use a pipette to inject 14μL of precursor solution into the slit. Set the parameters of the scraper: step length is 45000, step speed is 2800. Turn on the nitrogen air knife switch, control the flow rate at 30L / min, and then start scraping. After the scraping is completed, the substrate covered with the perovskite precursor film is quickly transferred to a hot stage at 120℃ and annealed for 45min to obtain a 3D perovskite film, i.e., a 3D perovskite layer.

[0083] (5) Preparation of hole transport layer

[0084] a. Prepare Spiro-OMeTAD precursor solution: weigh 0.0720 g Spiro-OMeTAD, add 17.5

[0085] μL Li-TFSI (the solution is 0.5200g Li-TFSI dissolved in 1mL acetonitrile solvent), 28.8μL tBP solution and 1mL chlorobenzene mixed solution, shake on a shaker at room temperature for 7-8h, then remove and keep away from light for later use.

[0086] b. Preparation of hole transport layer: spin coating the precursor liquid on the surface of ITO / SnO2 / seed layer / perovskite layer. Specifically, pre-spin the precursor liquid at 500 rpm for 3 seconds, and then spin coat the liquid film at 3000 rpm for 30 seconds to the substrate without annealing to obtain the hole transport layer.

[0087] (6) Preparation of metal electrode layer

[0088] A vacuum thermal evaporation method is used to evaporate a metal Ag electrode with a thickness of 100 nm on the surface of the deposited functional layers.

[0089] Example 3

[0090] A solar cell was prepared according to the steps of Example 2, except that CPAH was used instead of CBAH to prepare the 2D perovskite seed layer.

[0091] Comparative Example 1

[0092] A solar cell was prepared according to the steps of Example 2, except that the FAPbI3 perovskite layer was directly prepared on the SnO2 electron transport layer, and the 2D perovskite seed layer was discarded.

[0093] The photovoltaic performance of the solar cells prepared in Examples 2, 3 and Comparative Example 1 was tested. The results are shown in Tables 1 and Figure 6 .

[0094] Table 1

[0095] Group Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.04 24.02 79.13 19.95 Example 2 1.09 24.56 81.41 21.98 Example 3 1.08 24.38 79.45 20.99

[0096] The current-voltage (J-V) curves of the solar cell devices of Examples 2, 3 and Comparative Example 1 under reverse scanning are as follows: Figure 6 As shown in Table 1, it can be concluded that the 2D perovskite seed layer can effectively improve the photoelectric conversion efficiency of solar cells (from 19.95% to 21.98%), ensure good electron extraction capability, and increase the current density (Jsc) of the device from 24.02 mA / cm 2 Increased to 24.56mA / cm 2 The film quality is significantly improved, non-radiative recombination is significantly suppressed, and the open circuit voltage (Voc) of the device is increased from 1.04V to 1.09V.

[0097] Since the long-term stability of solar cell devices plays a decisive role in their further development and practical application, in order to evaluate the effect of the 2D perovskite seed layer on the stability of the device, the unpackaged battery was placed in a dark environment with a temperature of 25°C and a relative humidity of 25%, and the PCE changes of the device were continuously measured. Figure 7 The results show that the solar cell device of comparative example 1 drops to 63% of the initial PCE after 1992 hours, the device of example 3 only drops to 75% of the initial PCE after 1992 hours, and the device of example 2 still retains 80% of the initial PCE. The above results can be attributed to the protective effect of the 2D perovskite seed layer on the upper intrinsic perovskite, including reducing defects and improving crystallization.

[0098] Comparative Example 2

[0099] The solar cell was prepared according to the steps of Example 2, except that: CBAH solid powder was dissolved in DMF solvent at a concentration of 0.1 mmol / mL to prepare a seed precursor solution, and then the CBAH seed layer was prepared by spin coating on the surface of the SnO2 electron transport layer, and then the perovskite layer, the hole transport layer and the metal electrode layer were prepared in sequence on the surface; the other steps were the same as Example 2.

[0100] The photovoltaic performance of the perovskite solar cell prepared in Comparative Example 2 is shown in Table 2 and Figure 8 As shown, wherein Table 2 shows the comparison between it and the perovskite solar cell of Comparative Example 1, Figure 8 It shows the comparison with the perovskite solar cell of Example 2. It can be inferred from the experimental results that the method of Comparative Example 2 has no obvious effect on improving the crystal quality of the perovskite layer and the photovoltaic performance of the cell.

[0101] Table 2

[0102] Group Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.05 23.94 76.56 19.32 Comparative Example 2 1.04 23.83 75.01 18.73

[0103] Comparative Example 3

[0104] The solar cell was prepared according to the steps of Example 2, except that: the CBAH, PbI2, and FAI solid powders were directly mixed and dissolved in DMF in proportion to prepare a seed precursor solution, which was then spin-coated on the surface of the SnO2 electron transport layer to obtain a Mix seed layer, and then the perovskite layer, the hole transport layer, and the metal electrode layer were sequentially prepared on the surface thereof; the other steps were the same as in Example 2.

[0105] The photovoltaic performance of the perovskite solar cell prepared in Comparative Example 3 is shown in Table 3 and Fig. 9 As shown, wherein Table 3 shows the comparison between it and the perovskite solar cell of Comparative Example 1, Fig. 9 It shows a comparison with the perovskite solar cell of Example 2. It can be inferred from the experimental results that this method has no obvious effect on improving the crystal quality and photovoltaic performance of the perovskite layer.

[0106] Table 3

[0107] Group Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.11 22.77 78.66 19.92 Comparative Example 3 1.05 25.24 71.59 19.08

[0108] Comparative Example 4

[0109] Solar cells were prepared according to the steps of Example 2, except that the seed layer was discarded, and the CBAH solid powder was directly dissolved in the FAPbI3 perovskite precursor solution at a concentration of 0.1 mmol / mL, and the perovskite precursor solution was spin-coated on the surface of the SnO2 electron transport layer to prepare a CBAH-Add perovskite layer containing a CBAH additive, and then a hole transport layer and a metal electrode layer were sequentially prepared on the surface thereof; the other steps were the same as in Example 2.

[0110] The photovoltaic performance of the perovskite solar cell prepared in Comparative Example 4 is shown in Table 4 and Fig.10 As shown, wherein Table 4 shows the comparison between it and the perovskite solar cell of Comparative Example 1, Fig.10 It shows a comparison with the perovskite solar cell of Example 2. It can be inferred from the experimental results that this method has no obvious effect on improving the crystal quality and photovoltaic performance of the perovskite layer.

[0111] Table 4

[0112] Group Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.02 24.58 75.63 19.08 Comparative Example 4 0.99 24.78 70.66 17.39

[0113] The above experimental results show that only by introducing the 2D perovskite seed layer described in the present invention, especially the 4-SD seed layer, can the charge transport at the interface be effectively regulated, inducing the high growth orientation of FAPbI3 perovskite from bottom to top. The presence of the 2D perovskite seed layer effectively has a positive impact on the crystal growth process, significantly improving the morphology and crystal quality of the upper perovskite film, thereby achieving higher photoelectric conversion efficiency and stability of PSCs.

[0114] Example 4 Experimental study on process parameters for preparing seed layer

[0115] Test 1: Test of seed precursor solution concentration

[0116] Perovskite solar cells were prepared using seed precursor solutions with concentrations of 0.08 mmol / mL, 0.1 mmol / mL, 0.15 mmol / mL, and 0.2 mmol / mL, respectively. The other steps and parameters were the same as in Example 2. The perovskite solar cells prepared with seed precursor solutions of different concentrations were placed in a N2 atmosphere in a glove box for 3 h, and their changes were observed. The results are shown in FIG. Fig.11 .

[0117] like Fig.11 As shown, the perovskite solar cells prepared with 0.08mmol / mL and 0.1mmol / mL seed precursor solutions have better stability, while it can be clearly seen that the perovskite solar cells prepared with 0.15mmol / mL and 0.2mmol / mL seed precursor solutions show degradation; this indicates that a seed precursor solution concentration of 0.08-0.10mmol / mL is beneficial for the subsequent preparation of 3D perovskite layers.

[0118] Furthermore, the photovoltaic performance of perovskite solar cells prepared with 0.08 mmol / mL and 0.1 mmol / mL seed precursor solutions was tested; the results are shown in Table 5, and it can be seen that the perovskite solar cell prepared with 0.01 mmol / mL seed precursor solution has the highest efficiency, indicating that the optimal concentration of the seed precursor solution is 0.1 mmol / mL.

[0119] Table 5

[0120] Seed precursor solution concentration Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) 0.08mmol / mL 1.04 23.74 73.77 18.36 0.1mmol / mL 1.13 24.55 73.82 20.52

[0121] Test 2: Test for the optimal thickness of the seed layer

[0122] Based on the fact that the thickness of the seed layer is positively correlated with the amount of seed precursor solution, in order to determine the optimal thickness of the seed layer, the present invention uses 20 μL, 25 μL, 30 μL, and 35 μL seed precursor solutions to prepare perovskite solar cells of the same specifications, and the other steps and parameters are the same as those in Example 2; the photoelectric conversion efficiency of the perovskite solar cells prepared with different amounts of seed precursor solution is tested, and the results are shown in FIG. Fig.12 .

[0123] Fig.12 It shows that when the amount of seed precursor solution is 30 μL, the seed layer thickness is 200 nm, and the photoelectric conversion efficiency of the perovskite solar cell is significantly improved compared with other amounts. Therefore, the optimal thickness of the seed layer is determined to be 200 nm.

[0124] Experiment 3: Experiment on seed layer annealing temperature

[0125] The seed layer was prepared at annealing temperatures of 120°C and 150°C, respectively, and a FAPbI3 perovskite layer was prepared on the surface of the seed layer. Except for the annealing temperature of the seed layer, the other steps and parameters were the same as those in Example 2. The seed layer prepared at different annealing temperatures and the perovskite layer thereon were observed using a scanning electron microscope.

[0126] like Fig.13 As shown in (a), the 4-SD seed layer annealed at 120°C has a regular hexagonal seed morphology, while the 4-SD seed layer annealed at 150°C in 13(b) is disorderly and has many overlapping grains, which is almost destroyed. Fig.13 (c) Based on Fig.13 The perovskite layer prepared by the seed layer shown in (a) has a good crystal morphology, while in 13(d), it can be seen that the perovskite layer prepared based on the seed layer shown in 13(b) has obvious cracks, which damages the crystallization of the perovskite. Therefore, the optimal annealing temperature of the seed layer is 120°C.

[0127] The present invention may be summarized in other specific forms that do not violate the spirit or main features of the present invention. The above embodiments of the present invention can only be regarded as an explanation of the present invention rather than a limitation. Therefore, any minor modifications, equivalent changes and modifications made to the above embodiments based on the essential technology of the present invention are within the scope of the technical solution of the present invention.

Claims

1. A perovskite solar cell, comprising a stacked conductive glass layer, an electron transport layer, a perovskite layer, a hole transport layer, and a metal electrode layer, wherein the material of the perovskite layer is FAPbI3; wherein: Also included is a 2D perovskite seed layer disposed between the electron transport layer and the perovskite layer, which provides a nucleation site for the formation of an α-FAPbI3 phase of the perovskite layer; The 2D perovskite seed layer is prepared by the following steps: 1) dissolving organic amine, PbO and MACl in a mixed aqueous solution of HI and H3PO2, heating under stirring for reaction, and then cooling and precipitating to obtain a 2D perovskite seed single crystal; 2) making the 2D perovskite seed single crystal into a seed precursor solution, coating it on the surface of the electron transport layer, and annealing to obtain a 2D perovskite seed layer.

2. The perovskite solar cell according to claim 1, characterized in that: The organic amine is cyclopropylcarboxamidine hydrochloride or cyclobutanecarbonylamidine hydrochloride.

3. The perovskite solar cell according to claim 2, characterized in that: Organic amine, PbO and MACl were dissolved in a mixed aqueous solution of HI and H3PO2, so that the concentrations of organic amine, PbO and MACl in the solution were 0.1 mmol / mL, 3 mmol / mL and 0.02 mmol / mL, respectively.

4. The perovskite solar cell according to claim 3, characterized in that: The mixed aqueous solution of HI and H3PO2 is obtained by mixing an aqueous HI solution with a concentration of 57wt% and an aqueous H3PO2 solution with a concentration of 50wt% in a volume ratio of 6:

1.

5. The perovskite solar cell according to claim 4, characterized in that: The heating is to gradually increase the temperature from room temperature to 240° C. at a heating rate of 180 rpm / s. When the temperature reaches 240° C., the reaction is completed, and then cooling is performed to precipitate.

6. The perovskite solar cell according to claim 5, characterized in that: The thickness of the 2D perovskite seed layer is 200 nm.

7. The perovskite solar cell according to claim 6, characterized in that: The 2D perovskite seed single crystal was added into DMF solvent at a concentration of 0.08-0.10 mmol / mL and dissolved on a shaking table at room temperature for 7-8 hours to prepare a seed precursor solution.

8. The perovskite solar cell according to claim 7, characterized in that: The 2D perovskite seed single crystal was added into DMF solvent at a concentration of 0.10 mmol / mL and dissolved on a shaking table at room temperature for 7 to 8 hours to prepare a seed precursor solution.

9. The perovskite solar cell according to claim 8, characterized in that: The seed precursor liquid is coated by spin coating, specifically, the seed precursor liquid is pre-spun at 1000 rpm for 5 seconds, and then the liquid film is spun at 5000 rpm for 30 seconds to the electron transport layer, and then transferred to a heating table at 120° C. in a nitrogen atmosphere of a glove box, and annealed for 30 minutes to obtain a 2D perovskite seed layer.

Citation Information

Patent Citations

  • Perovskite solar cell based on SnO2 interface modification layer made of non-fullerene acceptor material and preparation method of perovskite solar cell

    CN116322093A

  • Preparation method of perovskite thin film and application of perovskite thin film in solar cell device

    CN117560979A

  • Surface passivation perovskite solar cell

    CN220476238U

Cited By

  • Perovskite solar cell and design method of interface fusion layer thereof

    CN122003014A